(untitled) (Psychology Travelogs, 2023)
The article examines the analysis of emotional intelligence of future psychologists as the basis of their professional competence. Each of the main levels of emotional intelligence is also considered: low, high and average. All emotions bring people together, they can be divided into good emotions and bad, but in any case it will be better appreciated by each other. When a person expresses an emotion, he always tries to convey other information. In the professional activity of a psychologist, it is very important to listen and experience (be competent), both bad and good emotions, because in each there is an action to rapprochement and understanding with the provision of help. In an effort to support or strengthen the psychologist’s cognitive, emotional and physical resources, the use of emotional intelligence is a modern tool of effective development, which allows the modern specialist to coordinate effective work with a large number of clients, which often represent a specific (unique) set of roles. Developed emotional intelligence is necessary for a psychologist in order to better feel clients, understand their emotional states, and establish effective and productive cooperation in the process of work. The conducted comparative analysis of the results of an empirical study of the levels of emotional intelligence of future psychologists makes it possible to draw conclusions that there is a noticeable positive dynamic with a significant predominance of a high level of EI among all studied students of higher education, which is a positive indicator of the professional competence of future psychologists. The comparative analysis of the results, carried out according to gender, shows that a high level of emotional intelligence prevails identically in the group of women and the group of men, which also gives grounds for predicting the personal professional effectiveness of the subjects in the future psychological professional activity, regardless of their gender.